On Jon Snow's death: Plot twist and global fandom in Game of Thrones. (September 2020) - Pérez, Héctor J; Reisenzein, Rainer
The death of Jon Snow at the end of the fifth season of the TV serial Game of Thrones prompted an intense reaction among the fans of the serial on social media. Thousands of viewers all over the world contributed to the discussion of the meaning and implications of this event, turning it into a global event in the participatory culture of contemporary seriality. In this article, we propose an explanation of this remarkable cultural phenomenon. Based on a theory of plot twists as surprise structures, we argue that the reactions of fans can be understood as concrete, contextually adapted realizations of the characteristic cognitive reactions evoked by the emotions of surprise and shock caused by unexpected negative events. Our analysis focuses in particular on the contributions of viewers to the establishment of the beliefs disconfirmed by the plot twist and on the cognitive activities that served to adapt their minds to the new reality revealed by the twist, which also included reflections on the aesthetic aspects of the plot twist and the narrative in which it was embedded. By providing a public platform for these reflections, the fan forums allowed the individual attempts to adapt to the plot twist to become a collective endeavor. The study illustrates how universal cognitive mechanisms interact with culturally produced contents to generate similar reactions to a fictional event across the globe.